PHYSICOCHEMICAL AND HEAVY METAL ANALYSIS OF THE LEAF, STEM AND FLOWER EXTRACTS OF SPHENOCLEA ZEYLANICA - GOWRI J; PRAGATHISWARAN C; AROCKIA SAHAYARAJ P (Innovare Journal of Sciences, 2017)
ABSTRACT Herbal traditional medicines play a principal role in health care programs especially in developing countries.WHO recommends various physicochemical and phytochemical evaluation parameters for quality control of medicinal plants are recommended by WHO.In pharmacognostic studies, identifying controversial species of plants, authentication of commonly used traditional medicinal plants through morphological, phytochemical and physicochemical analysis are done. In this study, physicochemical parameters, florescence and heavy metals of methanol extract of leaves, stem and flower of Sphenoclea zeylanica were conducted. It was seen that the properties and the results observed were significant and hence the plant S.zeylanicacan be used to formulate drugs to cure various diseases if the bioactive components are analyzed. Â Key words :Sphenoclea zeylanica physicochemical parameters, florescence and heavy metals